Review article: The use of Rabbinic sources in Gospel studies - Instone-Brewer, David (Tyndale bulletin, 1999)
New Testament scholars tend to avoid rabbinic sources because of the problem of dating. This is a genuine problem, but it is not insurmountable. The work of Neusner and others has highlighted this problem but it has also indicated some ways to deal with it. This review article looks at three recent books which demonstrate the usefulness of rabbinic background for studying the Gospels. All three have dealt with the problem of dating, with varying success. Brad Young has produced a useful book on the Parables, though he tends to compare them with the theology of post-Temple Judaism. Roger Aus’ studies sometimes suffer from parallelomania, though his investigation of the woman caught in adultery is masterful. Maurice Casey’s search for the Aramaic behind Mark leads him into creative and sometimes compelling arguments based on rabbinic texts. All three clearly believe that they can identify early rabbinic material and deal with it critically, and on the whole they appear to have succeeded. They have employed traditional scholarship, historical criticism and literary criticism. New Testament scholarship would greatly benefit from the additional use of redaction criticism of rabbinic material, as developed by Neusner and others.